O impacto das interações com o cliente no desempenho de novos produtos - Spasin , Paulo Eduardo (2015)
This work consists of replication and validation of the study by Bonner (2010) on customer interactivity and performance of new products in development projects. The initial study tested the relationship between the participation of the customer in new product development projects, the quality of customer information used in the projects and the impact of these dimensions on the performance of these products. Moreover, it was also established moderating effect caused by the newness of the product and the product's embeddedness on the client desktop. The original study was based on the communication literature and adopted an organizational learning vision based on the flow of communication. To validate this study in the Brazilian context was held to adapt the scale used by Bonner (2010) to portuguese language and used data collection with survey on a valid sample of 155 respondents from all over Brazil, belonging to the industrial sector, characterized by are machinery and equipment manufacturers. Data were analyzed with the use of structural equation modeling. The theoretical dimensions investigated were confirmed, and the relationships between them. The moderating effect caused by the newness of the product and embeddedness the product in the customer's work environment was also confirmed. As a result we obtained a valid instrument adapted to the Brazilian context.